The Empididae (Diptera) of Serbia: faunistic survey and description of a new Empis species - Shamshev, Igor V.; Ivković, Marija (Zootaxa, 2020)
The Empididae fauna of Serbia is summarised including currently 50 confirmed species belonging to nine genera: Clinocerinae—Kowarzia Mik (1), Phaeobalia Mik (2), Wiedemannia Zetterstedt (4); Empidinae—Empis Linnaeus (16), Hilara Meigen (11), Rhamphomyia Meigen (6); Hemerodromiinae—Chelifera Macquart (7), Hemerodromia Meigen (2), Phyllodromia Zetterstedt (1). A checklist of species is provided. Empis (Empis) serbica sp. nov. is described.